Document Delivery System at the National Information Centre for Food Science and Technology (NICFOS) - A Case Study - Krishnaswamy Rao, V.; Rammana, B.; Chennakesava Das, S. B. (Journal of Information and Knowledge, 2014)
Presents analysis of the document delivery services by NICFOS, Mysore during 1987. It indicated that there is need for translated articles from non-English languages. It also helped in setting priority for selection of periodical publication and other documents.